Determinants of Customer Retention During Pandemic - Humairoh Humairoh; Fina Karlina; Mohammad Annas (Universitas Muhammadiyah Tangerang, 2022)
This study aims to analyze the relationship between several variables store atmosphere, product quality, and personal selling to customer retention during the pandemic at Hypermart Puri Indah. This study uses a descriptive method with a quantitative approach. The sample in this study amounted to 100 respondents. Statistical tests were carried out which included simple regression tests, multiple regression tests, simple correlation tests, multiple correlation tests, and determination of the coefficient of determination. And the hypothesis test is also carried out which includes a T-test and F-test. The results showed that partially the store atmosphere variable had a positive and significant effect on customer retention. This is indicated by t stat > t table or 3,608 > 1,986 with a significant value of 0,000 < 0,05. Product quality has a positive and significant effect on customer Retention. This is indicated by t stat > t table or 6,177 > 1,986 with a significant value of 0,000 < 0,05. And personal selling has a positive and significant effect on customer retention. This is indicated by t stat > t table or 6,000 > 1,986 with a significant value of 0,000 < 0,05. And simultaneously variable store atmosphere, product quality, and personal selling. Namely F stat > F table of 38,732 > 2,70. With the value of the multiple regression equation, Y = 17,145 + 0,272X1 + 0,473X2 + 0,434X3 with a coefficient of determination of 53,3% while the remaining 46,7% is influenced by other variables outside the variables not discussed in this study.